PENYELESAIAN SENGKETA GUGATAN WAKAF MENURUT HUKUM PERDATA DAN HUKUM ISLAM - Prayogi, Prayogi; Astarudin, Tatang; Yusup, Deni Kamaludin (Gapenas Publisher, 2025)
This research is motivated by the increasing number of waqf lawsuit dispute cases in Indonesia which shows that there is an insynchronization between positive legal practices and Islamic law principles, especially in terms of the status of waqf property and the rights of the parties. The purpose of this research is to analyze the mechanism of dispute resolution of waqf lawsuits according to the perspective of civil law and Islamic law and evaluate its effectiveness in providing justice and legal certainty. This study uses a normative juridical approach with a descriptive analysis method. Data was collected through a literature study that included laws and regulations related to waqf, MUI fatwas, legal literature, and relevant court decisions. The analysis is carried out qualitatively through content analysis to identify the basic principles and implementation of dispute resolution. The results of the study show that civil law provides litigation space through district courts, while Islamic law prioritizes non-litigation approaches such as deliberation-based mediation (sulh), settlement by nadzir, and settlement through religious courts. This study recommends the need for harmonization between the civil law system and Islamic law as well as strengthening the role of nadzir institutions and the Indonesian Waqf Agency (BWI) in resolving disputes fairly and efficiently.